Clonal Transgenerational Effects of Parental Grazing Environment on Offspring Shade Avoidance - Jingjing Yin; Weibo Ren; Ellen L. Fry; Ke Xu; Kairi Qu; Kairu Gao; Hailong Bao; Fenghui Guo (Agronomy, 2024)
Grassland plants that endure livestock grazing exhibit a dwarf phenotype, which can be transmitted to clonal offspring. Yet to date, it remains poorly understood whether such transgenerational dwarf effects alter the plants’ response to shade. Here, we conducted a common garden experiment under sunlight and shade conditions with clonal Leymus chinensis offspring, the parents of which had endured livestock overgrazing (OG) and non-grazing (NG) in the field, respectively. Plant morphological, physiological, and transcriptomic analyses were carried out. The results indicated that NG offspring showed greater shade avoidance than OG offspring. That is, NG offspring exhibited greater plasticity of vegetative height and leaf width, which may be contributed to their greater photosynthetic capacity and gibberellin (GA3) content compared with OG offspring when treated with shade. In addition, RNA-Seq profiling showed that differentially expressed genes in NG offspring were mainly enriched in RNA modification and metabolic processes, which facilitated rapid response to shade. Phytochrome interacting factors (PIFs) promoted downstream shade marker genes in NG offspring by significantly downregulating the expression of PHYC, SPY, and DELLA. Our findings suggest that light conditions should be taken into account to better understand transgenerational dwarf effects induced by livestock grazing on grassland ecosystems. These results provide new insights into the inducible factors of phenotypic variations in grassland plants that experience grazing.